2018
DOI: 10.1097/gox.0000000000001699
|View full text |Cite
|
Sign up to set email alerts
|

Ketorolac May Increase Hematoma Risk in Reduction Mammaplasty: A Case-control Study

Abstract: Background:Ketorolac is a potent nonsteroidal anti-inflammatory drug that has valuable analgesic properties but also a hypothetical risk of increased bleeding due to inhibition of platelet activation. The clinical significance of this risk, however, is unclear when it is used after reduction mammaplasty. Our study objective was to therefore examine the association between ketorolac exposure and hematoma occurrence after breast reduction surgery. We hypothesized that there was no association between ketorolac e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…28 29 Barkho et al reported an increase in hematoma following reduction mammaplasty surgery and independent association with ketorolac use. 28 A retrospective analysis by Cawthorn et al also found that patients who received ketorolac had increased risk of hematoma. 29 In our study, hematoma rates were similar between ketorolac and nonketorolac groups, 5 (3 patients) and 3.6% (2 patients), respectively; there was no statistical significance ( p = 1.0).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 29 Barkho et al reported an increase in hematoma following reduction mammaplasty surgery and independent association with ketorolac use. 28 A retrospective analysis by Cawthorn et al also found that patients who received ketorolac had increased risk of hematoma. 29 In our study, hematoma rates were similar between ketorolac and nonketorolac groups, 5 (3 patients) and 3.6% (2 patients), respectively; there was no statistical significance ( p = 1.0).…”
Section: Discussionmentioning
confidence: 99%
“…27 Over the last decade, studies have reported an increased postoperative risk of hematoma with ketorolac use. 28,29 Barkho et al reported an increase in hematoma following reduction mammaplasty surgery and independent association with ketorolac use. 28 A retrospective analysis by Cawthorn et al also found that patients who received ketorolac had increased risk of hematoma.…”
Section: Discussionmentioning
confidence: 99%
“…39 In this case, the correct study design would be a case-control design. 40 Investigators should collaborate with a biostatistician when determining which study design best answers their research question.…”
Section: Precondition 2: Choose the Correct Study Design To Answer Yo...mentioning
confidence: 99%
“…Two studies 85,86 found only a slightly increased risk of hematoma associated with perioperative ketorolac that was nonsignificant in otherwise healthy patients. Two additional studies 87,88 showed a minimally increased risk of developing a hematoma after reduction mammaplasty in women who were administered perioperative ketorolac. Further research is needed before conclusions can be drawn about the risk-tobenefit comparison of ketorolac.…”
Section: Rationalementioning
confidence: 99%